Barriers Against Seeking Professional Care for Perceived Mental Stress among Medical Undergraduate Students: A Cross-sectional Survey at a Private Medical University of Islamabad: Barriers Against Seeking Professional Care for Perceived Mental Stress - Zulfiqar, Shaista; Shukr, Usman Irfan; Khan, Jawaria; Baig, Faisal Amin; Waheed, Aamir; Habib, Muhammad Farrukh; Raisani, Sher Afgan (Pakistan Journal of Health Sciences, 2024)
Medical students persistently face a burden of stress which may be a risk factor for depression, suicide, or substance abuse. Objectives: To assess barriers in seeking professional care for perceived mental stress in medical undergraduate students and to assess their stress. Methods: A cross-sectional survey was designed and conducted for six months. Using stratified random sampling, 41 medical students were selected from all five years. A structured questionnaire was used which included a modified BACE 3 scale to find frequencies of perceived barriers and PSS scale to assess perceived stress. Chi square test was applied to look for associations. Ethical approval and informed consent were taken. Results: Out of 205 respondents, 78 (24.4%) were male and 127 (75.6%) were female. Mean age was 21 years ± 1.69 SD. 76.96% of respondents reported experiencing moderate stress. Among all years, third year students (26.8%) reported the highest level of severe stress. The barrier reported by majority students was that students wished to solve the issue on their own (72.7%), second was that the issue would resolve by itself (45.4%). The barriers that were considered least frequently, were being unsure where to get help (19%) followed by being too sick to ask for help (18.5%). Chi square test showed significant association between categories of stress and year of education with a significant p value. Conclusions: Majority of the students faced moderate stress. However, when dealing with it, the majority wanted to solve the problem on their own.